Smart Green Box Trash Design Based on HC-SR04 Sensor Arduino Uno Integrated - Dika, Mahardika Setiawan; Suciyati, Sri Wahyu; Supriyanto, Amir; Pauzi, Gurum Ahmad (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
This research has realized the design of a smart green trash box based on the HC-SR04 sensor, which is integrated with Arduino Uno. This research aims to design and build a digital instrumentation system based on Arduino Uno, applying Ultrasonic Sensors to the Green Box Trash System. In addition, this system is equipped with an information display via LCD and speakers so that we can find out the contents of the green trash box. Data retrieval by detecting objects with a distance of less than 10 cm to open the trash and measure the volume in the green trash box. The research results are displayed as a prototype Smart Green Trash Box design. Based on the HC-SR04 Sensor Integrated by Arduino Uno. The ultrasonic sensor in the Green Box Trash system works well by measuring the volume and can detect when an object is approaching with a distance of less than 10 cm. Assembling the green box using the HC-SR04 sensor, which is integrated with Arduino Uno functions according to the program created if, in the green box, there is HC-SR04 1 sensor trash, it measure the volume of trash and then display it through the LCD, and if there is an object approaching the HC-SR04 sensor 2, then the servo moves so that the green trash box can be opened. The Green Trash box can display trash volume and time on the 16x2 character LCD in real-time with the program uploaded to Arduino as monitoring.